Pets in the workplace: a scoping review - Gardner DH (Informa UK Limited, trading as Taylor & Francis Group, 2024)
There is a large and growing body of literature proposing that there are benefits to employees and workplaces when pets are allowed to accompany their owners to work. This article reports a scoping review of research that is workplace-based and that provides information on the reported benefits or problems of allowing employees' pets at work. The databases Scopus, Discover and Google Scholar were searched with the initial search terms "pets AND workplace AND research." Results were reviewed initially by title to remove items where, for instance, "PET" was used as an acronym. Studies were included if they provided information on research into human well-being and/or work or task performance and pets at work. This included research into the presence of pets while working from home, as the home can be considered a workplace in this situation. A total of 189 papers on pets at work were identified from the searches. The abstracts were reviewed and papers that did not report research into the benefits and challenges of employees' pets at work were excluded, leaving 31 results. The majority of studies used survey methods and did not include validated psychometric measures of key variables including stress. Findings indicated that the presence of employees' pets at work may reduce stress and lead to more positive work-related attitudes, but these findings may not apply to all employees or all workplaces. Negative aspects of pets in the workplace include health risks to humans and animals, cultural concerns and dislike or fear of some animals, and the proportion of participants who raised these concerns or agreed with them varied widely between studies. However, there is little evidence on the prevalence of risks or how they are addressed, and there was no data on how work performance, absenteeism or staff turnover were related to pet-friendly policies at work. More research is required, and some directions for future research are suggested.
Keywords: Pets at work; human health; stress; well-being; Animals; Pets; Workplace; Humans